Prevention of renal damage caused by Shiga toxin type 2: Action of Miglustat on human endothelial and epithelial cells. (October 2015) - Girard, Magalí C.; Sacerdoti, Flavia; Rivera, Fulton P.; Repetto, Horacio A.; Ibarra, Cristina; Amaral, María M.
Abstract: Typical hemolytic uremic syndrome (HUS) is responsible for acute and chronic renal failure in children younger than 5 years old in Argentina. Renal damages have been associated with Shiga toxin type 1 and/or 2 (Stx1, Stx2) produced by Escherichia coli O157:H7, although strains expressing Stx2 are highly prevalent in Argentina. Human glomerular endothelial cells (HGEC) and proximal tubule epithelial cells are very Stx-sensitive since they express high levels of Stx receptor (Gb3). Nowadays, there is no available therapy to protect patients from acute toxin-mediated cellular injury. New strategies have been developed based on the Gb3 biosynthesis inhibition through blocking the enzyme glucosylceramide (GL1) synthase. We assayed the action of a GL1 inhibitor (Miglustat: MG), on the prevention of the renal damage induced by Stx2. HGEC primary cultures and HK-2 cell line were pre-treated with MG and then incubated with Stx2. HK- 2 and HGEC express Gb3 and MG was able to decrease the levels of this receptor. As a consequence, both types of cells were protected from Stx2 cytotoxicity and morphology damage. MG was able to avoid Stx2 effects in human renal cells and could be a feasible strategy to protect kidney tissues from the cytotoxic effects of Stx2 in vivo . Highlights: We assayed the action of MG on HGEC and HK-2 before treatment with Stx2. Miglustat protects renal cells viability from Stx2 toxicity. Miglustat decreases Gb3 expression on HK-2 and HGEC. Miglustat prevents morphologic alterations induced by Stx2 on HGEC and HK-2 cells.